Recent advances in therapeutic modalities and vaccines to counter COVID-19/SARS-CoV-2 - Muhammad Bilal; Hafiz M. N. Iqbal (Taylor & Francis Group, 2020)
The novel coronavirus disease (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has rapidly spread across the world. This resulted an alarming number of fatalities with millions of confirmed infected cases, pretending severe public health, economic, and social threats. There is no specific therapeutic drugs or licensed vaccines or treatments to fight against lethal COVID-19 infections. Given the significant threats of COVID-19, the global organizations are racing to identify epidemiological and pathogenic mechanisms of COVID-19 to find treatment regimens and effective therapeutic modalities for future prevention. Herein, we reviewed the therapeutic interventions and vaccines for COVID-19 based on the existing knowledge and understanding of similar coronaviruses, including MERS-CoV and SARS-CoV. The information constitutes a paramount intellectual basis to sustenance ongoing research for the discovery of vaccines and therapeutic agents. This review signifies the most available frontiers in the viral vaccine development approaches to counter the COVID-19/SARS-CoV-2.